El principio de favorabilidad en el delito de tenencia ilegal de armas - Salinas, Hernán Onofre (2012)
In this paper conducted an analytical study of the constitutional principle of favorability in the crime of illegal possession of weapons, taking into account that this offense is a figure of abstract danger, which is expected in two contradicting laws in form as described, as in the sanction imposed, creating a contradiction that I believe the first born of the contradictions of these two statutes, and that this leads to violation of the principle of lenity, because there are legal scholars who say that the found a person carrying a firearm without a permit, you should apply the provisions of Article 162 of the Penal Code, protected by the principle of lenity, and others that must be implemented as enacted in article 31 of the Manufacture of Weapons Act, in accordance with the principle of specialty.